The conservation of wisent In Westpomeranian region (European Bison Conservation Newsletter, 2010)
The paper presents situation of two European bison herds created in Westpomeranian region. First one in Mirosławiec Forestry was established in year 1980 trough releasing of 8 animals and restocking this group with 8 imported specimens in 2005. The second herd exists on the military area in Drawsko Forestry and consisted two previously separated groups released in year 2008. Up to now three projects were realized aiming to increase the population size, create the feeding infrastructure and introduce the telemetry method to improve management. In August 2009 the next project was prepared and at July 28,2010 the agreement with Center of Environment Projects was signed. The main aim of the project is increase of population size and its genetic variability, develop better public acceptance and ensure the proper health status of the herds.
Keywords: European bison; Westpomeranian; management; project